Healthcare associated coronavirus disease 2019 among health care workers in Normandy, France: a multi-center study. Issue 1 (March 2021) - Thibon, Pascal; Breton, Pierre; Mouet, Audrey; Bidon, Antoine; Haupais, François; Darrigan, Caroline; Gautier, Pauline; Letourneur, Thomas; Perillieux, Emeline; Seguineau, Charles; Thibon, Paul; Henry, Liliane; et al.
Summary: Introduction: In the early phase of the coronavirus disease (COVID-19) epidemic in France, knowledge of SARS-COV-2 characteristics was limited, and personal protective equipment (PPE) was lacking. Thus, health care workers (HCWs) were exposed to nosocomial transmission. Methods: A multicenter regional descriptive study of fifty-two heath care facilities covering 30, 533 HCWs in western Normandy, France, from March 3 to March 27, 2020, before the incidence threshold of 10/100, 000 inhabitants was crossed in the study area. The incidence rate of COVID-19 in HCWs, the attack rates and the serial interval distribution of nosocomial transmission were computed. Demographic characteristics of HCWs, contacts with index cases, and the use of personal protective equipment were collected by a structured questionnaire. Results: The incidence rate of COVID-19 in HCWs was 2.7‰. Among 19 situations (13 clusters >2 cases), 10 were HCW-HCW and 9 patient-HCW transmission, the global attack rate was 13.7% (95% confidence interval, 10.6%–17.3%), and 68 HCWs were involved (10 index cases, with 58 secondary cases). Exposure of secondary cases was only in the presymptomatic phase of the index case in 29% of cases, 48% for HCW-HCW and 10% for patient-HCW transmission ( P <0.001). The mean serial interval was 5.1 days (95% CI, 4.2–5.9 days). Preventative measures were not optimal. Conclusions: Our investigation demonstrated that HCWs who were not assigned to the care of COVID-19 patients were not prepared for the arrival of this particularly insidious new virus, which spread rapidly from an often asymptomatic colleague or patient.